The Northwest Geysers EGS Demonstration Project, California – Part 2: Modeling and interpretation. (September 2016) - Rutqvist, Jonny; Jeanne, Pierre; Dobson, Patrick F.; Garcia, Julio; Hartline, Craig; Hutchings, Lawrence; Singh, Ankit; Vasco, Donald W.; Walters, Mark
Graphical abstract: Highlights: Geomechanical modeling of cool water injection into very hot rock. Modeling reasonably predicted the extent of the stimulation zone. A shear-zone network was identified from daily microseismic evolution. Evaluated relative contribution from temperature and pressure effects. Identified stimulation-induced mechanical degradation and porosity change. Abstract: In this paper, we summarize the results of coupled thermal, hydraulic, and mechanical (THM) modeling in support of the Northwest Geysers EGS Demonstration Project, which aims at enhancing production from a known High Temperature Reservoir (HTR) (280–400 °C) located under the conventional (240 °C) geothermal steam reservoir. The THM modeling was conducted to investigate geomechanical effects of cold-water injection during the stimulation of the EGS, first to predict the extent of the stimulation zone for a given injection schedule, and then to conduct interpretive analyses of the actual stimulation. By using a calibrated THM model based on historic injection and microseismic data at a nearby well, we could reasonably predict the extent of the stimulation zone around the injection well, at least for the first few months of injection. However, observed microseismic evolution and pressure responses over the one-year stimulation-injection revealed more heterogeneous behavior as a result of more complex geology, including a network of shear zones. Therefore, for an interpretive analysis of the one-year stimulation campaign, we included two sets of vertical shear zones within the model; a set of more permeable NW-striking shear zones and a set of less permeable NE-striking shear zones. Our modeling indicates that the microseismic events in this system are related to shear reactivation of pre-existing fractures, triggered by the combined effects of injection-induced cooling around the injection well and rapid (but small) changes in steam pressure as far as a kilometer from the injection well. Overall, the integrated monitoring and modeling of microseismicity, ground surface deformations, reservoir pressure, fluid chemical composition, and seismic tomography depict an EGS system hydraulically bounded by some of the NE-striking low permeability shear zones, with the more permeable NW-striking shear zone providing liquid flow paths for stimulation deep (several kilometers) down into the HTR. The modeling indicates that a significant mechanical degradation (damage) inferred from seismic tomography, and potential changes in fracture porosity inferred from cross-well pressure responses, are related to shear rupture in the stimulation zone driven by both pressure and cooling effects.